Examining the Spatial Disequilibrium and Driving Factors of Population Aging and Elderly Service Resource Allocation in Rural Areas: A Case Study of Wenzhou City - Xiang Xiaoye; Lin Liyue; Xu Shiyu; Huang Tao (Redai dili)
Based on seventh population census data, Point Of Interest (POI) data, road network data, elevation data, and night light index, we used the entropy method, nuclear density analysis method, spatial dislocation index, geographic detector, and other methods to study the phenomenon and driving factors of population aging and the spatial disequilibrium of pension service resources in each township (street) of Wenzhou in 2020. This research plays a positive role in realizing the fine allocation of resources for elderly care facilities at the township level in Wenzhou City, improving elderly care service facilities in urban and rural areas, and promoting the equalization of public service facilities at the township and village levels. The results can be summarized as follows: 1) As Wenzhou enters a deeply aging society, the spatial distribution of the elderly population, elderly population density, population aging coefficient, elderly population support ratio, and comprehensive aging index are basically the same, showing a gradually increasing spatial pattern from the municipal district to the peripheral streets of the municipal district to the remote towns; 2) Elderly care service resources in Wenzhou present an asymmetrical and unbalanced north-south spatial distribution pattern with the municipal districts as " diversified supply in municipal streets, basic guarantee in developed coastal towns, and shortage of supply in inland mountainous towns "; 3) The streets of the municipal district have rich elderly care service resources, including Grade 3 general hospitals and comprehensive nursing homes, to provide diversified elderly care services for the elderly in the municipal district; there are many old-age care facilities such as hospitals, clinics, and nursing homes in Ruian, Yueqing City, and central towns such as Hongqiao and Aojiang, which provide basic old-age security for the elderly in and around the area. In the northern part of Yongjia County, Wencheng County, Taishun County, and other remote towns and villages, the number of old-age medical resources and facility resources is scarce, and the accessibility of health centers and nursing homes to residents in marginal villages is low, which makes it inconvenient for the elderly to see a doctor in time and enjoy professional old-age services; 4) The size of the elderly population, nighttime Light Index, and road network density are the main driving factors causing the spatial imbalance of elderly service resources in the townships (streets) of Wenzhou City. Specific suggestions based on this study are as follows: Wenzhou should break the restraints of administrative divisions, speed up the process of co-construction and sharing of elderly care service resources between Lucheng District, Ouhai District, Longwan District and Yongjia County, southern townships of Yueqing City and eastern streets of Ruian City, achieve cross-regional linkage of elderly care facilities, improve the utilization rate of elderly care service resources, and prevent the situation of idle elderly care service resources; financial support for deeply aging towns in Wencheng County, Taishun County and Yongjia County should be increased, the construction of elderly care facilities in remote towns and health service consulting and cross-regional medical security capabilities of the elderly population in towns and cities should be increased, and the gap between the elderly service resources and the level of elderly care services in developed towns and cities should be narrowed; Yueqing City, Longgang City, Cangnan County, and Pingyang County should coordinate the existing resources, use the stock of land, combine urban renewal and the transformation of old urban communities, accelerate the construction of public infrastructure such as health service stations, nursing homes, leisure squares, and green parks within the 15-minute life circle of neighboring communities, and constantly improve the suitability of elderly care service resources for the elderly population.